MicroRNA-155 Controls T Helper Cell Activation During Viral Infection - Goncalves-Alves, Eliana; Saferding, Victoria; Schliehe, Christopher; Benson, Robert; Kurowska-Stolarska, Mariola; Brunner, Julia Stefanie; Puchner, Antonia; Podesser, Bruno K.; Smolen, Josef S.; Redlich, Kurt; Bonelli, Michael; Brewer, James; et al. (Frontiers in Immunology, 2019)
MicroRNA (miR) 155 has been implicated in the regulation of innate and adaptive immunity as well as autoimmune processes. Importantly, it has been shown to regulate certain antiviral responses, but its contribution to the immune response against cytopathic viruses such as vesicular stomatitis virus (VSV) infections is not known. Using transgenic/recombinant VSV expressing ovalbumin, we show that miR-155 is crucially involved in regulating the T helper cell response against this virus. Our experiments indicate that miR-155 in CD4+ T cells controls their activation, proliferation and cytokine production in vitro and in vivo upon immunization with OVA as well as during VSV viral infection. Using intravital multiphoton microscopy we analyzed the interaction of antigen presenting cells (APCs) and T cells after OVA immunization and found impaired complex formation when using miR-155 deficient CD4+ T cells compared to wildtype CD4+ T cells ex vivo. In contrast, miR-155 was dispensable for the maturation of myeloid APCs and for their T cell stimulatory capacity. Our data provide the first evidence that miR-155 is required for efficient CD4+ T cell activation during anti-viral defense by allowing robust APC-T cell interaction required for activation and cytokine production of virus specific T cells.